The normalization of sexual diversity in revolutionary Cuba - Kirk, Emily J. (2015)
Cuba, once understood to be a highly homophobic country, has been lauded internationally for its attention to sexual diversity rights since 2008. This Thesis examines and analyzes the development of the normalization of attitudes towards sexual diversity in revolutionary Cuba. This includes the evolution of homophobia in Cuba, the Federation of Cuban Women’s development of sexual education, the establishment of the Nation Centre for Sexual Education (CENESEX), and how these elements engage with the island’s view of health. In particular, the thesis focuses on two main questions: how did attitudes towards sexual diversity evolve in Cuba? And what does this evolutionary process tell us about the Revolution?